2012
DOI: 10.1080/09603123.2011.634389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical exercise and gender on acetylcholinesterase and butyrylcholinesterase activity in human blood samples

Abstract: The determination of cholinesterase activity in plasma and erythrocytes serves as a useful and sensitive biomarker of exposure to organophosphorus and carbamate pesticides. However, acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) activity may be influenced by factors such as age, gender, drugs, and physical exercise. The aim of this study was to evaluate the effects of gender and physical exercise on the activity of AChE and BuChE in healthy individuals. The values for both enzymes were lower for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
2
8
1
5
Order By: Relevance
“…The elevation in BChE activity in response to exercise supports previous findings suggesting that an acute bout of walking/running elevated plasma BChE activity (16). The mechanisms underlying this response require further study, though it may be that the transient increase in inflammatory markers could be implicated (34).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The elevation in BChE activity in response to exercise supports previous findings suggesting that an acute bout of walking/running elevated plasma BChE activity (16). The mechanisms underlying this response require further study, though it may be that the transient increase in inflammatory markers could be implicated (34).…”
Section: Discussionsupporting
confidence: 86%
“…However, less is known about the interplay between BChE, FTO rs9939609 and exercise in humans. One study indicated that a single bout of light running increases BChE activity in humans (16), but further work is needed to examine if BChE activity is linked to FTO rs9939609 genotype and exercise-dependent changes in plasma ghrelin concentrations or appetite-related outcomes in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Although results from our study are not consistent within diverse statistical test, other study confirm our main finding, that physical activity influence change of AChE activity, although the study was conducted on younger population and short term activity with significant difference between genders [33]. Moreover, this study is in the accordance to the finding that concentration and activity range is not dependent on age and gender, but it is not in the accordance of usage non parametric tests based on included participants [34].…”
Section: Discussioncontrasting
confidence: 73%
“…In healthy human subjects, swimming increase enzyme AChE activity [Piech M, 2017]. In adult (22.5+-3.0 years) single session of physical activity does not cause the effect on enzyme AChE activity, but in adolescent (17.5+-0.6 years), it does [Zimmer KR, 2012; Schulpis KH, 2007]. Changes in enzyme AChE activity during a few days, months and years of storage is known for healthy subjects [Freitas Leal JK, 2017; Crane CR, 1970].…”
Section: Discussionmentioning
confidence: 99%
“…Otra investigación, también realizada en ratas, estudió el comportamiento de la expresión de ChE y su relación con la fatiga [16], sin embargo, existe poca información sobre la actividad de las ChE en la actividad física en humanos. Hay dos estudios recientes [20,21], pero que no relacionan los cambios de las ChE con ningún efecto sobre la fatiga.…”
Section: Introductionunclassified